Sylvian fissure meningioma: A case report and systematic review of clinical and surgical insights - Mohammed A. Azab; Khalid Sarhan; Oday Atallah; Ahmed Sabra; Brahim Kammoun; Ahmed Hazim; Sara Hamed; Mohsen Nabih Shama (Brain and Spine, 2025)
Background: Meningothelial cells within the arachnoid of the Sylvian fissure give rise to a rare subtype of non-dural based tumors known as Sylvian fissure meningiomas (SFMs). The clinical presentations and management of these lesions need to be further explained. Methods: We followed the PRISMA statement guidelines when reporting this systematic review and meta-analysis. We conducted a literature search through PubMed, Embase, and Web of Science. Databases: We performed a quantitative summary of all included studies. We also describe an additional case report of a grade II Sylvian fissure meningioma (SFM). Results: A total of 40 patients with sylvian fissure meningioma were analyzed. The mean (range) age was 23.4 (1.5–73) years, 24 were adults and 16 were children with a female-to-male ratio of 15:25. Most patients with Sylvian fissure meningioma (SFM) presented with seizures 28 (70 %). According to the WHO histological grading of meningiomas, a total of 32 (80 %) tumors were diagnosed as grade I meningiomas and 8 (20 %) were WHO grade II. Pterional craniotomy was the most frequently employed approach, 21 (67.7 %). In 35 studies reporting surgical resection outcomes, gross total resection was achieved in 25 (71.4 %) patients, whereas subtotal resection was necessary in 10 (28.6 %) patients. Postoperative complications were present in 10 out of 40 patients. Conclusion: WHO grade II SFMs are a rare subset of supratentorial meningiomas. The most common symptom is seizure. Imaging reveals no dural tail like other typical meningioma characteristics. The cornerstone of therapy is surgery. It is necessary to assess whether such a location has a positive or negative predictive value in larger case series cohorts.